Emerging Trends in the Transmission Pathways of Nipah virus: A Comprehensive Review - Neha, D; Nikita Dung Dung; Anju Thomas; Jeas John (Gayaku Publisher, 2024)
Nipah virus (NiV), a highly pathogenic zoonotic virus belonging to the Paramyxoviridae family and Henipavirus genus, was first identified during an outbreak in Malaysia in 1998-1999 and has since been reported in South and Southeast Asia, primarily in Bangladesh and India. The virus is transmitted through zoonotic spillover from animal reservoirs, particularly fruit bats (Pteropus species), as well as human-to-human transmission. Pigs can become infected by consuming fruits contaminated by infected bats, and humans can contract the virus through contact with infected pigs or bats. This review provides a comprehensive overview of the transmission dynamics of Nipah virus, emphasizing zoonotic spillover, direct contact with infected animals, and human-to-human transmission during outbreaks. Understanding these transmission pathways is essential for developing effective control and prevention strategies. NiV outbreaks have occurred in Malaysia, Singapore, Bangladesh, India, and the Philippines, often resulting in severe respiratory and neurological diseases with high mortality rates in both humans and pigs. Diagnosis of Nipah virus infection involves various techniques, including serological, molecular, virological, and immunohistochemistry methods. The potential for human-to-human transmission poses a significant public health concern, highlighting the need for improved diagnostic and surveillance measures..